Identifikasi Genetik Kultivar Padi Gogo dengan Menggunakan Marka RAPD - Simarmata, Marulak; Rustikawati, Rustikawati (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2015)
A research was conducted to identify the genetics of upland rice cultivars using random amplified polimorphic DNA (RAPD) markers. Five out of 60 random primers that capable to amplify the most number of markers were OPE-07 (AGATGCAGCC), OPE-15 (ACGCACAACG), OPH-13 (GACGCCACAC), OPH19 (CTGACCAGCC), and OPM-02 (ACAACGCCTC). The number of markers amplified were 5, 6, 8, 8, and 7, respectively. RAPD-PCR using these 5 primers arranged to DNA templates of 41 rice cultivars amplified 1127 RAPD markers. Polymorphic information content (PIC) of each primer were 0.79, 0.80, 0.87, 0.87, and 0.72, respectively. Cluster analysis using a UPGMA dendogram showed that the 41 cultivars were grouped into 9 clusters with genetic similarity index more than 90 percent.